Occurrence of pathogenic Vibrio cholerae serogroups O1 and O139 in some estuaries of Tanzania - Temba, David; Namkinga, Lucy; Moyo, Sabrina; Lyimo, Thomas J.; Lugomela, Charles V. (Tanzania Journal of Science, 2021)
In this study, the occurrence of culturable Vibrio cholerae serogroup O1 and O139 in three selected Tanzanian Estuaries, Mzinga, Pangani and Ruvu were explored. A total of 480 water and plankton samples were collected along salinity gradients (fresh, brackish and marine waters). Samples were enriched in Alkaline Peptone Water (APW) and subsequently cultured on Thiosulfate Citrate Bile-Salt Sucrose (TCBS) agar. Resulting isolates were serially identified by oxidase test, API-20E test and monoclonal antibodies for V. cholerae serogroup O1 and O139. A total of 670 presumptive V. cholerae isolates were obtained from 416 samples (86.7%), where 137 (20.4%) were oxidase test positive. Out of the oxidase test positive, 96 (70.8%) were further confirmed by API 20E to be V. cholerae while only 8 isolates were ascertained by monoclonal antibodies to be V. cholerae O1 and 1 isolate to be V. cholerae O139. This indicated that, apart from the few V. cholerae O1 and O139 confirmed serogroups, there is still a large percentage of V. cholerae non-O1/O139. Similarly, both V. Cholerae serogroups O1 and non-O1/O139 were observed in clinical samples suggesting a close link between the existence of the bacterium in aquatic environments and cholera outbreak. Keywords: Tanzanian Estuaries, V. cholerae, serogroupO1/O139